Effect of interactive learning media: numeral snakes and ladders on clock reading and arithmetic operation for elementary students - Noviafitri, Kartika Satya; Huda, Miftakhul; Mukti, Taufiq Satria; Binti Yahya, Faridah Hanim (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
Learning media is important to support student learning achievements. Numeral Snakes and Ladders (NSL) is an interactive learning media innovation for elementary schools with an interesting and fun cooperative learning approach for students. This research aims to determine the effectiveness of media in learning and improve students' understanding of basic data literacy. The research used a quantitative approach with a quasi-experimental design. NSL Media was implemented at SDN Gebanganom, Kangkung District, Kendal Regency, with the entire student population in grade 4 and grade 5. Data collection was carried out using direct tests. The sampling technique for this research is saturated sampling. Data analysis was carried out using a paired sample T-test. The research results showed that by testing using the paired sample T-test, evidence was <0.05 obtained that the two groups before and after using NSL media experienced a significant increase. Apart from that, learning using NSL media can affect students' cognitive abilities, the effect can be concluded from the test increase from 78.2 to 82.1. The characteristics of students observed during the learning process are honesty, responsibility, and spiritual attitudes well developed. Apart from that, teachers can develop and direct social and spiritual skills and attitudes in learning in the hope that students can grow and develop according to their phases and have quality learning outcomes.